Education Unit Strategies in Increasing Students' Interest in Participating in Religious Extracurricular Activities at School - Heri Kristianto; Agus Susetyo; Ferdian Utama; Eko Nani Fitriono; Siti Roudhotul Jannah (Bulletin of Pedagogical Research, 2023)
Education is a must for a nation because education is a way to educate the nation's life. The education process does not only take place formally but can also be obtained through organizations in schools. Organizationally in the school environment, there is a religious extracurricular, Rohis, which provides positive student activities. However, the right strategy is needed so that students are motivated to participate in a series of activities in religious extracurricular activities. So the problem formulation is how the education unit strategy to increase student interest in participating in Rohis religious extracurricular activities at school. This research was conducted at SMP N 9 Metro and using qualitative methodology: data were obtained through interviews with the education unit and extracurricular school administrators, observation, and documentation. The results of this study explain that convincing students of things according to their needs by using the advice method and providing guidance by encouraging students to understand and practice the teachings of Islam correctly by using the technique of exemplary, habituation, punishment, reward, and attention, encouraging students to understand and practice Iman, Islam, and Ihsan with actualization and application in daily life using the method of habituation, exemplary, and attention. Keywords: Education Unit Strategies, Students' Interest, Religious Extracurricular